2009
DOI: 10.1523/jneurosci.1863-09.2009
|View full text |Cite
|
Sign up to set email alerts
|

Differential Activity-Dependent Secretion of Brain-Derived Neurotrophic Factor from Axon and Dendrite

Abstract: Brain-derived neurotrophic factor (BDNF) is essential for neuronal survival and differentiation during development and for synaptic function and plasticity in the mature brain. BDNF-containing vesicles are widely distributed and bidirectionally transported in neurons, and secreted BDNF can act on both presynaptic and postsynaptic cells. Activity-dependent BDNF secretion from neuronal cultures has been reported, but it remains unknown where the primary site of BDNF secretion is and whether neuronal activity can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

26
266
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 237 publications
(293 citation statements)
references
References 68 publications
26
266
0
1
Order By: Relevance
“…We have thus focused our attention on BDNF-QD secretion at the dendrite. Studies using cultured hippocampal neurons expressing fluorescently tagged-BDNF have shown BDNF secretion at both axons and dendrites (45,46). However, BDNF and its propeptide have been found in presynaptic dense core vesicles, but not in the postsynaptic dendrites of the adult mouse hippocampus (6), suggesting an anterograde mode of action of BDNF.…”
Section: Discussionmentioning
confidence: 99%
“…We have thus focused our attention on BDNF-QD secretion at the dendrite. Studies using cultured hippocampal neurons expressing fluorescently tagged-BDNF have shown BDNF secretion at both axons and dendrites (45,46). However, BDNF and its propeptide have been found in presynaptic dense core vesicles, but not in the postsynaptic dendrites of the adult mouse hippocampus (6), suggesting an anterograde mode of action of BDNF.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, hippocampal slices from BDNF heterozygous mice displayed a significant decline of CAF LTP compared with WT. Previous experimental findings indicate that BDNF may be released at both pre‐ and postsynaptic levels (Lessmann & Brigadski 2009; Matsuda et al 2009; Edelmann et al 2014) and it is known that BDNF can significantly affect PPF (Kang & Schuman 1995). In our experiments, caffeine perfusion induced a significant change in PPF response suggesting an enhancement of the neurotransmitter release.…”
Section: Discussionmentioning
confidence: 99%
“…It also exhibits a neurotrophic action on the development of GABAergic interneurons and their networks in the cerebral cortex (13)(14)(15) and hippocampus (16,17). BDNF is secreted from DCV-like secretory vesicles from neuronal dendrites and axons (18). Together with CAPS2, synaptotagmin-IV also controls BDNF secretion, although these two proteins act in opposite ways: CAPS2 promotes secretion (7,8), whereas synaptotagmin-IV inhibits secretion (19).…”
mentioning
confidence: 99%